Sekoper Cinta: Perempuan dalam Wacana Pembangunan di Jawa Barat 2020 - Zahrah Izzaturrahim (Prodi Antropologi Fakultas Ilmu Budaya Universitas Diponegoro, 2021)
The high number of women population is not followed by women's empowerment, one of which is indicated by the low role of women in the public sector. This means that attention to issues related to women is actually still lacking, indicating the need to increase the role of women in development and their capabilities. Women's schools are one of the efforts that were originally initiated by activists to empower women through critical education at the grass root level. Over time, the state (in this context the local government) began to adapt these ideas into development discourse, as was done by the West Java Provincial Government with the Women's School Achieve Dreams and Dreams (Sekoper Cinta) program, in order to realize gender justice in life family, community, and state because the concept of women's schools is seen as very strategic to be able to overcome various social problems. This paper contains my analysis of the module or design of the Sekoper Cinta program—supported by literature studies and in-depth interviews with one of the Sekoper Cinta masters of training—using gender analysis related to agency to find out how the state defines women through an explanation of what types of programs can be implemented. accessible to women, whether the concept initiated by the government is in line with the ideas of the activists or does it indicate an indication of the application of the ideology of ibuism. Based on the results of the analysis, the concept of Sekoper Cinta is quite sensitive to gender issues where the program can describe the role of women in the structure of society. Furthermore, critical education designed in the module has positioned women as agents at the micro level (grassroots) capable of empowering themselves, their families, and their environment.